Identity and support for policies towards Indigenous people: Evidence from Australia - Astghik Mavisakalyan; Yashar Tarverdi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper adds to knowledge on the role of politicians' and voters' identities in influencing policy-making in societies marked by ethnic inequality. The outcome we investigate is the initiatives and policies targeting Indigenous populations in the context of Australia. We ask whether and how politicians' and voters' identities, defined based on a range of their observable characteristics, shape initiation and support of Indigenous-focused policies. Drawing on data on the voting history of members of the two houses of the Australian parliament, we provide an analysis of law-making behaviour and show that political ideology, and to some extent politicians' propensity to act rebelliously and diligently, are significant determinants of their agreement on Indigenous-focused policies. Our complementary analysis of voters' attitudes and preferences on issues concerning Indigenous Australians points to the high relevance of political ideology, and in doing so, highlights the alignments in the behaviours of politicians and voters.
Keywords: D70; J15; P16; 330; politician identity; voter preferences; political ideology; ethnic inequality; law-making; Indigenous Australians